Employer Branding and Its Dimensions: A Pilot Study in Higher Educational Institutions of Pakistan - Muhammad Awais Ilyas; Hasnizam Shaari; Ahmad Said Ibrahim Alshuaibi (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
The purpose of this paper is a pilot assessment to determine the validity and reliability of the instrument of employer branding dimensions namely training and development, employer brand reputation, work life balance and organization culture developed by Tanwar and Prasad (2016). The survey approach was used to collect response through 61 usable questionnaires from the academic staff of higher educational institutions located in Punjab which is largest populated province of Pakistan. The present study used the simple random sampling method in data collection. Then, the validity and reliability of items of employer branding dimensions were assessed through expert’s opinions both from academicians and practitioners and also from the small size sample data. The SPSS v20 was used to test the reliability in this study. Hence, the results of pilot study reveals that, the Cronbach’s alpha values of all constructs are above than 0.80, so it can establish that all the constructs of employer branding are reliable and no need to remove any item.